Integrasi Dakwah dalam Fungsi Pengawasan untuk Meningkatkan Kualitas Pelayanan Haji dan Umrah di PT Manajemen Qolbu Tauhiid Travel - Muhamad A, Ramadhan; Sugiarto (Prodi Manajemen Dakwah Fakultas Dakwah dan Ilmu Komunikasi Universitas PTIQ Jakarta, 2025)
The study explores the integration of dakwah principles into supervisory functions to enhance the quality of Hajj and Umrah services at PT Manajemen Qolbu Tauhiid Travel Jakarta. This qualitative descriptive research was conducted at the company, known for organizing religious pilgrimages under the guidance of KH Abdullah Gymnastiar's teachings from the Daarut Tauhiid foundation. Data were gathered through observations, in-depth interviews with staff and pilgrims, and analysis of internal documents. The results demonstrate that incorporating dakwah into supervision—such as requiring employees to attend regular Islamic studies, monitor daily worship through mutaba'ah yaumiyah, and instill values like 5S (smile, greet, address, polite, courteous) and 5AS (hard work, smart work, quality work, complete work, sincere work)—effectively boosts operational efficiency and ethical service delivery. This model not only surpasses pilgrims' expectations by providing premium accommodations, comprehensive guidance, and spiritual enrichment but also mitigates common challenges in the industry, including delays, substandard facilities, and misconduct. The integration fosters a work environment rooted in tauhid and morality, leading to higher pilgrim satisfaction and sustainable improvements. The study offers practical insights for other travel agencies to adopt dakwah-based oversight for superior, spiritually aligned services in the Hajj and Umrah sector.